Hyperactivation of HER2-SHCBP1-PLK1 axis promotes tumor cell mitosis and impairs trastuzumab sensitivity to gastric cancer - Wengui Shi (Nature Portfolio, 2021)
Resistance to Trastuzumab in HER2 gastric cancer patients remains a clinical challenge. In this study, the authors demonstrate that HER2 promotes tumorigenesis in gastric cancer by regulating mitotic progression through a Shc1-SHCBP1-PLK1-MISP axis and they identify a compound, TFBG, able to disrupt SHCBP1/PLK1 interaction and to synergize with trastuzumab.